2003
DOI: 10.1007/s00415-003-0235-9
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of lower motor neuron syndromes

Abstract: This review discusses the most important lower motor neuron syndromes. This relatively rare group of syndromes has not been well described clinically. Two subgroups can be distinguished: patients in whom motor neurons (lower motor neuron disease (LMND)) are primarily affected or motor axons and their surrounding myelin (multifocal motor neuropathy (MMN)), both leading to muscle atrophy and weakness. Both hereditary and sporadic forms of LMND have been described. The discussion of recent advances in the genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 231 publications
1
32
0
Order By: Relevance
“…The differential diagnosis of MMN includes two different categories of disorders: motor-neuron disease 2,13,14,28,[39][40][41][42][43] and demyelinating neuropathies.…”
Section: Differential Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…The differential diagnosis of MMN includes two different categories of disorders: motor-neuron disease 2,13,14,28,[39][40][41][42][43] and demyelinating neuropathies.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] The disorder was thought to be immune mediated, possibly through IgM antibodies that bind gangliosides on human peripheral nerves. 12 The differential diagnosis of MMN includes motor-neuron disease 13,14 and demyelinating neuropathies. [15][16][17] Diagnosis of MMN is supported by the finding of motor but not of sensory abnormalities on nerve-conduction studies.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, postmortem studies showed Bunina bodies, which are common morphological features of PMA and the classic form of ALS. 5,9 Given the rarity of HypoPP and PMA, a chance association of the CACNA1S mutation and this phenotype was unlikely. Furthermore, the daughter of the index patient (III:4, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3 Most cases of PMA are linked both clinically and pathologically to amyotrophic lateral sclerosis (ALS). 5,9 Herein we report a patient with familial HypoPP and PMA that had a fatal course. The disorder was associated with the R528H mutation in the calcium channel protein Cav1.1.…”
mentioning
confidence: 97%